Analysis of Environmental Health Risk of So2, No2, Nh3, and Dust Exposure In Sentra Industri Surabaya, Gresik And Sidoarjo City - Bintang Aji Pangestu; R. Azizah; Rica Naudita Krisna Setioningrum (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Every process of industrial activity generates potential waste as air pollutants. Air pollution needs to be analyzed to estimate the magnitude of the risk posed. The purpose of this study was to investigate environmental health risks in exposure to SO2, NO2, NH3, and dust gases for workers in Surabaya, Gresik, and Sidoarjo. The method of this research is by collecting secondary data was obtained from BBTKLPP Surabaya. The secondary data collected was calculated using the Environmental Health Risk Analysis (ARKL) method by finding the concentration value, the amount of intake, and the characteristics of the maximum and minimum health risks of each chemical agent in the air parameters in the work environment. The research results show that the concentrations of exposure to SO2, NO2, NH3, and dust in the safe category at the industrial centers of Surabaya, Gresik, and Sidoarjo for workers.